DERACIALISATION! WHAT DERACIALISATION?: THERE’S NO END TO RACE (Review article) - Ndlovu, Siyanda (PINS-Psychology in Society, 2025)
Reviewing A race against time (2006) 2010, four years after its publication, is perhaps a blessing in disguise. Such an accidental, critical distance is a significant opportunity to reflect, as one chapter in the book suggests, on “the role, nature, utility and longevity of race” (Bowman, Seedat, Duncan and Burrows, 2006: 91) in the landscape of post-apartheid South Africa. A landscape that once held so much promise and hope of something “new” and “better”, of a “rainbow nation” united in its diversity and unrelenting in its moral quest for human rights, equality, social justice and of course its national vision of non-racialism. So, we must, as the book attempts to, ask the question, how far have we come in achieving the promise of non-racialism and the dream of deracialisation? Since the book’s publication in 2006, there has been what Hall (1996) in his work on identity, refers to as, a “discursive explosion”, in the national, political and public imagination around “race” and all its varieties in South Africa. It is useful to briefly reflect on and take stock of some of the events and debates that have happened in the post-apartheid landscapes since the book first appeared on book shelves.